2021
DOI: 10.3390/ncrna7020034
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs in the Control of Gametogenesis: Lessons from Fission Yeast

Abstract: Long non-coding RNAs (lncRNAs) contribute to cell fate decisions by modulating genome expression and stability. In the fission yeast Schizosaccharomyces pombe, the transition from mitosis to meiosis results in a marked remodeling of gene expression profiles, which ultimately ensures gamete production and inheritance of genetic information to the offspring. This key developmental process involves a set of dedicated lncRNAs that shape cell cycle-dependent transcriptomes through a variety of mechanisms, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 103 publications
(180 reference statements)
0
5
0
Order By: Relevance
“…The binding site for Mei2 in Erh1 has not been established yet but, since Mmi1 is also present in this dot and might form EMC, it seems that the S. pombe ERH (Erh1) could also interact simultaneously with two partners there [122,132]. Mei2 and Mmi1 also interact indirectly via binding to some lncRNAs, including meiRNA encoded by the sme2 gene, at which locus the dot is formed [133][134][135].…”
Section: Data Inferred From Partners Of the Proteinmentioning
confidence: 97%
“…The binding site for Mei2 in Erh1 has not been established yet but, since Mmi1 is also present in this dot and might form EMC, it seems that the S. pombe ERH (Erh1) could also interact simultaneously with two partners there [122,132]. Mei2 and Mmi1 also interact indirectly via binding to some lncRNAs, including meiRNA encoded by the sme2 gene, at which locus the dot is formed [133][134][135].…”
Section: Data Inferred From Partners Of the Proteinmentioning
confidence: 97%
“…Most characterized lncRNAs function sequence independently by forming tertiary structures and interacting with proteins as a scaffold ( Yoon et al, 2013 ; Andric and Rougemaille, 2021 ). Dozens of protein partners of lncRNAs have been reported ( Gerstberger et al, 2014 ), among which the PRC2 (Polycomb Repressive Complex 2) complex has been well-studied.…”
Section: The Biogenesis and Function Of Lncrnamentioning
confidence: 99%
“…One early study suggests a regulatory role of anti-sense lncRNA during the mitosis-to-meiosis transition [ 77 ]. Later studies identified a set of functional lncRNAs that regulate meiotic-specific chromosomal events at the transcriptional or post-transcriptional level [ 78 ]. Considering the potentially larger pool of lncRNAs and their complicated regulation in higher eukaryote systems, we reason that a considerable portion of lncRNAs perform a function in meiosis, which has yet to be explored.…”
Section: Opportunities and Challengesmentioning
confidence: 99%